How to make psychedelic-assisted therapy safer - Villiger, D (Cambridge University Press, 2024)
Classic serotonergic psychedelics are experiencing a clinical revival, which has also revived ethical debates about psychedelic-assisted therapy. A particular issue here is how to prepare and protect patients from the vulnerability that the psychedelic state creates. This paper first examines how this vulnerability manifests itself, revealing that it results from an impairment of autonomy: psychedelics diminish decision-making capacity, reduce controllability, and limit resistance to external influences. It then analyzes the strengths and weaknesses of five safety measures proposed in the literature, what aspect of the patient’s vulnerability they seek to reduce, and how they can be optimized. The analysis shows that while preparatory sessions, advance directives, and specific training and oversight are useful, starting with a lower dosage and no therapy is less so. Finally, the paper presents a safety measure that has been overlooked in the literature but could be highly effective and feasible: bringing a close person to the psychedelic session.